2004
DOI: 10.1038/labinvest.3700065
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent perivascular inflammation induced by lipopolysaccharide (endotoxin) results in the formation of atheromatous lesions in vivo

Abstract: Bacteria and viruses are suspected to induce arteriosclerosis; however, most investigators have focused on coincidences rather than causal relationships. The aim of this work was to establish a rabbit model in which the vessel reaction to local perivascular injection of defined bacterial products can be analyzed. A total of 23 rabbits were randomized to four groups. Groups A and B were fed a normal diet, groups C and D were fed a cholesterolenriched diet. Groups A and C were treated with a single perivascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 25 publications
(22 reference statements)
0
17
0
Order By: Relevance
“…Some proinflammatory factors, such as lipopolysaccharide (LPS), trigger the inflammation response and promote the generation of inflammatory cytokines by VSMCs 1 and are demonstrated to be involved in atherogenesis. 2 Increased inflammatory cytokine activity promotes infiltration of inflammatory cells and then augments the inflammatory response. 3 VSMCs in the medial wall of blood vessels are normally quiescent and express a differentiated phenotype to generate and maintain vascular tone.…”
mentioning
confidence: 99%
“…Some proinflammatory factors, such as lipopolysaccharide (LPS), trigger the inflammation response and promote the generation of inflammatory cytokines by VSMCs 1 and are demonstrated to be involved in atherogenesis. 2 Increased inflammatory cytokine activity promotes infiltration of inflammatory cells and then augments the inflammatory response. 3 VSMCs in the medial wall of blood vessels are normally quiescent and express a differentiated phenotype to generate and maintain vascular tone.…”
mentioning
confidence: 99%
“…43 Transient migration of VSMCs into neointima resulting from perivascular inflammation using LPS from E. coli in normocholesterolemic rabbits has been described previously by our group. 19 Further studies on lesion initiation during the early phase of the inflammatory injury are needed as we did not observe significant presence of inflammatory cells after 16 weeks of repeated infections using CPN either in its viable or in inactivated form. Moreover, the local inoculation of fractionated bacterial components will allow identification of atherogenic factors.…”
Section: Discussionmentioning
confidence: 73%
“…Intima media ratio was calculated from the measured area of intima and area of media, and lesion area index from the lesion area related to the area of media, as published previously. 19 To prevent bias from an operator-dependent effect, morphometric analyses were performed independently of the operator (MGE) by CVR who was blinded towards the perivascular treatment performed.…”
Section: Histopathological Studiesmentioning
confidence: 99%
“…Several studies have reported that repeated injections of endotoxin in animals significantly accelerates atherosclerosis, suggesting that LPS-induced immune mechanisms play an important role in the atherosclerotic process 5,23,24) . The findings of the present study are consistent with those of the above studies, although they are in direct contrast with the results of earlier studies in which no proatherogenic effects of endotoxin administration were observed in piglets or rabbits fed a high-cholesterol diet 25,26) .…”
Section: Discussionmentioning
confidence: 99%